The strength of (comics) drawings as a documentary form of war, misery and trauma (KULT_online, 2016)
Starting from a historical study of the graphic representation of disasters beginning with the works of Jacques Callot and Fransisco Goya, the main focus of Disaster Drawn is to analyze and read drawn disaster in contemporary comics. Based on the work of world-famous graphic artists Keiji Nakazawa, Art Spiegelman, and Joe Sacco, the medium of comics is considered as an appropriate and fruitful way to document history, in particular of war and trauma. The book is rich in biographical information about the artists, detailed analyses of primary works, and elaborations on the consequences disastrous events may have on the aesthetic and ethical dimensions of comics.